2012
DOI: 10.1158/0008-5472.can-12-0481
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10 Promotes Osteolytic Bone Metastasis by Enhancing Cancer Outgrowth and Osteoclastogenesis

Abstract: Amplification of the chemokines CXCL10 and RANKL has been suggested to promote osteoclast differentiation and osteolytic bone metastasis, but a function for endogenous CXCL10 in these processes is not well established. In this study, we show that endogenous CXCL10 is critical to recruit cancer cells to bone, support osteoclast differentiation and promote for the formation of osteolytic bone metastases. Neutralizing CXCL10 antibody reduced migration of cancer cells expressing the CXCL10 receptor CXCR3, and loss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 35 publications
3
82
1
Order By: Relevance
“…30, 31, 32, 33, 34, 35, 36, 37, 38 The localization of CXCR3 in tumor cells, endothelial cells and tumor-infiltrating lymphocytes in our HGSC samples matches earlier results in clear cell ovarian cancer. 39 By using splice variant-specific antibodies, Furuya et al 39 demonstrated that endothelial cells mainly expressed CXCR3-B, whereas cancer cells mainly expressed CXCR3-A.…”
Section: Discussionsupporting
confidence: 89%
“…30, 31, 32, 33, 34, 35, 36, 37, 38 The localization of CXCR3 in tumor cells, endothelial cells and tumor-infiltrating lymphocytes in our HGSC samples matches earlier results in clear cell ovarian cancer. 39 By using splice variant-specific antibodies, Furuya et al 39 demonstrated that endothelial cells mainly expressed CXCR3-B, whereas cancer cells mainly expressed CXCR3-A.…”
Section: Discussionsupporting
confidence: 89%
“…We found that transcripts of CCL5, CCL9 and CXCL10 increased 12-, 6.8-, and 4.5-fold, respectively, in Colon26L5-CUG2 cells compared to those in Colon26L5-Vec cells (data not shown). Many lines of evidence have supported that CCL5, CCL9 and CXCL10 are involved in metastasis of various cancer cells (27)(28)(29), and have shown that IFN signaling induces upregulation of these chemokines (30)(31)(32). We therefore assume that upregulated chemokines through the STAT1-IFN axis enhance migration of colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, C-X-C motif chemokine 10 (CXCL10) has been reported to facilitate the trafficking of C-X-C chemokine receptor type 3 (CXCR3)-expressing cancer cells to bone, which augments its own production, enhances tumor growth and at the same time promotes osteoclastic differentiation, indicating that the CXCL10/CXCR3 axis may be another attractive therapeutic target for osteolytic metastasis [61]. …”
Section: Homing To the Bonementioning
confidence: 99%